(untitled) (Proceedings of the International Conference on Education, 2025)
In today’s digital age, students can easily learn English through immersive activities that extend beyond the confines of traditional classroom settings. Known as Extramural English (EE), this practice has been seen as useful for enhancing English proficiency development. Thus, integrating EE into English Language Teaching (ELT) has become a priority for teachers worldwide. Nonetheless, little exploration of EE has been conducted in Indonesian schools. To fill this gap, this phenomenological study aims to explore how Indonesian English as a Foreign Language (EFL) teachers perceive the role of EE in their students’ English learning. The data were collected through semi-structured interviews with six EFL teachers, selected purposively based on varying criteria, including diverse teaching levels, regions (i.e., Sulawesi, Java, Sumatra), types of schools (i.e., public and private schools), and teaching experiences. Through phenomenological analysis, it was found that teachers had positive attitudes toward EE since it helped them overcome traditional classroom limitations. From their views, EE offered various benefits, such as providing enjoyable learning and authentic input, increasing students’ motivation and confidence, and improving vocabulary and English skills. Meanwhile, the challenges included the absence of objective assessment, a lack of technology assistance, parental concerns, and difficulty choosing appropriate learning materials. This study offers crucial insights into educational approaches that encourage EE practice in the teaching and learning process to increase students’ English exposure and ease of learning.